Data Mining Regarding Cyberbullying in the Arabic Language on Instagram Using KNIME and Orange Tools - Alzahrani, S. S. (Engineering, Technology & Applied Science Research, 2022)
This paper deals with data mining on verbal bullying by Instagram users. It tracks people who repeatedly have abusive behavior and may cause harm to other persons or groups. In this work, a dataset holding verbal bullying in the Arabic language was extracted from Instagram comments, and the entries were classified as regular verbal bullying and suspicious verbal bullying. KINIME and Orange open source data mining tools were utilized to discover comments that involved verbal bullying on Instagram and to delete previous comments while users sent their comments automatically and immediately. Classification algorithms Rule-Based in KNIME and Select Rows in Orange were used.